Battery doctor ‐ next generation battery health assessment: Definition, approaches, challenges and opportunities - Zhao Yang Dong; Zhijun Zhang; Rui Zhang; Tianjing Wang (Energy Conversion and Economics)
Abstract A new concept of battery doctor is proposed for the next generation battery health assessment, first, the comprehensive assessment framework integrating the multiple health indices is formulated, where the bottom‐up assessment hierarchy is used to provide the holistic health indicator from the battery cell to the large‐format battery. Second, several options for defining a uniform indicator state of X is provided to effectively measure the battery health, which contributes to promoting the health assessment from state of charge and stage of health to state of X. Finally, the future challenges and opportunities of developing the battery doctor are disclosed from three different viewpoints, which is to incentivize the technology breakthrough for the next generation battery health assessment.